1998
DOI: 10.1002/(sici)1096-9063(199806)53:2<133::aid-ps756>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant effect, biological efficacy and high affinity binding of imidacloprid to acetylcholine receptors inMyzus persicaeandMyzus nicotianae

Abstract: : It is known from laboratory studies that tobacco-associated forms of Myzus persicae (Sulzer) and the closely related tobacco aphid Myzus nicotianae (Blackman) are often somewhat less susceptible to imidacloprid than nontobacco strains of M. persicae. Choice tests (Ñoating leaf technique) showed that tobacco aphids were also less susceptible to the antifeedant potential of imidacloprid in contact bioassays. Synergists like piperonyl butoxide or DEF did not enhance the susceptibility of tobacco-associated morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 18 publications
3
49
0
6
Order By: Relevance
“…It is most commonly used on rice, cereal, maize, sunflowers, potatoes and vegetables. It is applied as a seed and soil treatment, crop and structural treatment, and a topical flea control treatment on domestic pets [1][2][3][4][5]. It is also used for animal health applications to control parasites like fleas of dogs and cats [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is most commonly used on rice, cereal, maize, sunflowers, potatoes and vegetables. It is applied as a seed and soil treatment, crop and structural treatment, and a topical flea control treatment on domestic pets [1][2][3][4][5]. It is also used for animal health applications to control parasites like fleas of dogs and cats [6].…”
Section: Introductionmentioning
confidence: 99%
“…The knockdown effect of pyrethroids on insects are well known. Imidacloprid is widely used as a systemic insecticide to control piercing-sucking insects (Nauen et al 1998;1999), including sharpshooters in citrus orchards and vineyards Castle et al 2005;Byrne & Toscano 2006;Byrne & Toscano 2007). The contact effect of imidacloprid, causing high sharpshooter mortality within a short period of time, is described here for the first time.…”
Section: Discussionmentioning
confidence: 96%
“…Previous investigations have shown that continuous feeding for approximately 30 min on infected trees is required to successfully acquire the pathogen, and 5-7 h of feeding on trees is required to transmit the pathogen to healthy plants ( Grafton-Cardwell et al 2013). Therefore, the spread of HLB may be reduced by deterring the vector from feeding on citrus plants (Chiyaka et al 2012;Nakasuji et al 1975;Nauen 1995;Nauen et al 1998), which serve as hosts for both the pathogen and the vector. The present study indicated that afidopyropen acts as a feeding deterrent against D. citri.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to sublethal insecticide concentrations is known to cause physiological changes that reduce development and fecundity and lead to an overall fitness decline in certain insect species (Harnoto et al 1984;Luckey 1968;Omer and Leigh 1995;Stark and Banks 2003). In general, exposure of hemipteran species to sublethal insecticide concentrations reduces feeding, growth, survival, and reproduction (Kerns and Stewart 2000;Lee et al 1988;Nauen et al 1998). Alternatively, exposure to sublethal concentrations may increase fecundity by stimulating reproduction through hormoligosis, which increases fitness (Chen and Nakasuji 2004;.…”
Section: Discussionmentioning
confidence: 99%